OPTIMIZING SOCIAL MEDIA FOR PROMOTING SMALL AND MEDIUM ENTERPRISES IN MALANG REGENCY - Mubarok, Faiz Ushbah; Riatma, Galih Putra; Rahmanto, Anugrah Nur; Asri, Atiqah Nurul; Ananta, Ahmadi Yuli; Arianto, Rakhmat; Nurhasan, Usman (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Singajaya Futsal Center (SFC) is an indoor sports facility located in Putat Kidul village, Gondanglegi sub-district, Malang regency. It has established since 2011 and aimed to provide an indoor futsal for the local community. Even though the Singajaya Futsal Center has been operating for almost 12 years, this facility has not used social media in marketing and promotion. Thus, the officers also have difficulties in reaching the right target audience. Thus, the number of visitors who come is not stable yet. Currently, SFC is trying to improve the quality of service and quality of facilities. In addition, it also strives to improve the quality of promotional and marketing content on social media. With that, the business hopes to increase the number and provide the best quality service to visitors. However, the owner is starting to realize that social media is an effective marketing tool nowadays. They started to think about using social media in promotion and marketing. Additionally, they still have to figure out the right way to use social media and evaluate its effectiveness. The results of this PPM activity create appropriate and attractive social media for visitors. In addition, employees also got the opportunity to directly manage and promote using social media.